'Stretched But Not Snapped': A Response to Russell and Serban on Retiring the 'Westminster Model'. Issue 2 (3rd April 2022) - Flinders, Matthew; Judge, David; Rhodes, R.A.W.; Vatter, Adrian
Abstract: This article engages with Meg Russell and Ruxandra Serban's (2021 ) argument that the Westminster model is 'a concept stretched beyond repair' that deserves 'to be retired'. We examine the logic, theory and methods that led to such a powerful, potent and provocative argument. We suggest their approach may have inadvertently 'muddied' an already muddled concept. We assess the implications of 'muddying' for their conclusion that the Westminster model is, in essence, a dead concept in need of a decent funeral. We suggest the concept is 'stretched but not snapped' by developing a simple four-perspective broadening of the analytical lens. This approach aids understanding about what the concept covers, how it is operationalized and why it remains useful in comparative research.